Further Investigations of the Social and Material Convoy: Exploring Relationships between Race, Volunteering, and Relocation. (6th October 2018) - Perry, Tam E; Shen, Huei-Wern; Gonzales, Ernest
Abstract: This study used the social and material convoy framework to explore how individual and social resources, including volunteer engagement, inform household transitions in later life by race. Data from the 2008 and 2010 Health and Retirement Study compared non-Hispanic whites' and non-Hispanic blacks' relocation patterns in 2010 ( N = 8, 361). Multinomial logistic regression models tested the relationships between economic, home environment, health, social, and sociodemographic variables with relocation by race. Greater household assets, poorer health, and changing marital status reduced the likelihood of moving out of area among older white adults. However, home ownership and education reduced older black adults' likelihood of out-of-area relocation. The social and material convoy framework demonstrated racial heterogeneity as older white adults who formally volunteered in 2008 were less likely to move out of area in 2010. Although policies on formal volunteering could help older white adults age in place, the same approach may not influence older black adults.